Development of post conditioning injection molding process control on glass filled nylon (polyamide 6) composites for global product engineering - Abdul Rahman, Abdul Azim (2019)
The wide use of glass filled nylon (Polyamide 6) composites material in office furniture industry has put higher demands on engineers to conduct more accurate and increasingly sophisticated analysis of materials in order to endure the performance of the molded parts under the end-use conditions characterized by varying humidity, temperature, and dynamic load or deformation. Glass Filled Nylon (Polyamide 6) Composites is a hygroscopic material where it is very sensitive to moisture which is an important factor to be considered during material pre-selection, parts design, mechanical performance prediction, testing and evaluation process. The effect of moisture can be a major factor in products and parts evaluation that were exposed to different weather conditions due to changing in seasons or geographic locations. Due to this effect of moisture absorption in uncontrolled condition, rejection % increased from 3% to 20% due to inconsistent of testing results during in process inspection. This also caused some of the production lot to be quarantined until further verification. This resulted loss and reduced of the profit of the company as well as wastage of material and resources. The research focused on process control of conditioning the nylon parts and components after molded before proceeding with testing and evaluation. Post Conditioning machine was developed for quantify the optimize process control of Glass Filled Nylon (Polyamide 6) Composites parts. These process control covered a wide range for 3 process parameters for conditioning; temperature (from 20 to 80-degree C), relative humidity (from 30% to 80% RH) and time (unlimited variables control). The variation of these parameters may result in significantly different moisture absorption rates, equilibrium levels and mechanical properties. The results comprehensive up to date information and critical understanding on the impact of moisture and temperature on testing and evaluation of Glass Filled Nylon (Polyamide 6) Composites parts and components. This method of the post conditioned machine accelerated the moisture absorption from 0.001 percent to 0.125 percent which is incremental by 12,400 percent compare to current industry practice. This able to stabilize the parts in short time and able to proceed for evaluation. It will give better recommendations on process control of conditioning the nylon parts and components to make sure that all the testing and evaluation result valid and standardize between different seasons and geographical locations.